Naiadacarus sidorchukae sp. n. (Acariformes: Acaridae) from Western Siberia closely related to a North American species, with a new generic synonymy - Klimov, Pavel B.; Oconnor, Barry C.; Khaustov, Alexander A. (Zootaxa, 2019)
A new species of acarid mite, Naiadacarus sidorchukae sp. n., is described from phoretic deutonymphs collected from a European spruce bark beetle, Ips typographus, pheromone trap in Western Siberia, Russia. Morphologically, the new species is very similar to the North American species, Naiadacarus fashingi, with the only diagnostic character being the shorter tibial solenidion φ II in the former species. Unlike some Naiadacarus species, which are truly aquatic, Naiadacarus sidorchukae probably does not inhabit fully aquatic habitats. This species and other presumably non-aquatic taxa, may represent the ancestral condition in the genus Naiadacarus, and, therefore are critical in studying land to water ecological transitions that have occurred in this mite genus. The monotypic genus Naiacus Nesbitt, 1990 is considered as a junior synonym of Naiadacarus Fashing, 1974 (syn. n.), with its type-species, Naiacus muertensis Nesbitt, 1990, recombined as Naiadacarus muertensis (Nesbitt, 1990), comb. n. A key to species of Naiadacarus of the world is provided